Elephant population trends and associated factors: a review of the situation in western Ghana - Danquah, Emmanuel; Oppong, Samuel (Pachyderm, 2013)
The Ankasa and Bia Conservation Areas and the Goaso Forest Block form a significant portion of forest elephant range in western Ghana. This paper reviews historical and recent information on elephant population trends in western Ghana and the factors associated with these trends. We used two methods: 1) monitoring trends in elephant populations using density estimates, and 2) tracking changes in elephant distribution and density due to poaching activity. Our results indicate that most elephant populations have declined in western Ghana, although a few seem to have persisted. Specifically, we recorded positive trends in two protected areas, Ankasa and Bia, where elephants seem to be recovering under good management practices, such as reduced hunting pressure and habitat management. The Goaso elephant populations have suffered major declines in both numbers and range. Currently, elephant range is confined to only a few of the reserves in the northern Goaso Forest Block. These declines were probably as a consequence of accelerated immigration of farmers into Ghana’s western region in the 1990s, resulting in increased hunting activity and habitat loss due to unregulated timber extraction and agriculture. We also show that effective elephant range is negatively affected by poaching activity, and that elephants currently do not move across the Ghana–Cote d’Ivoire boundary. Additional key words: Ankasa, Bia, Goaso Forest, poaching activity, elephant conservation Les aires de conservation d’Ankasa et de Bia et le bloc forestier de Goaso constituent une partie importante de l’habitat des éléphants de forêt dans l’ouest du Ghana. Ici, nous passons en revue les données historiques et récentes sur les tendances des populations d’éléphants dans l’ouest du Ghana et les facteurs y associés. Nous avons utilisé deux méthodes 1) le suivi des tendances des populations d’éléphants en utilisant les estimations de densité et 2) le suivi des changements concernant la distribution et la densité des éléphants par rapport au braconnage. Nos résultats indiquent que la plupart des populations d’éléphants ont diminué dans l’ouest du Ghana, bien que quelques-unes semblent avoir persisté. Plus précisément, nous avons constaté des tendances positives dans deux aires protégées, Ankasa et Bia, où les éléphants semblent se rétablir grâce aux bonnes pratiques de gestion (par exemple, une pression de chasse réduite et une gestion de l’habitat). D’autre part, les populations d’éléphants de Goaso ont subi des baisses importantes en nombre et en habitat. À l’heure actuelle, l’habitat des éléphants se limite à seulement certaines réserves dans le bloc forestier nord de Goaso. Ces baisses étaient probablement une conséquence de l’immigration accélérée des agriculteurs dans la région ouest du Ghana dans les années 1990 donnant lieu à une activité de chasse accrue et une perte de l’habitat due à l’exploitation du bois non réglementée et à l’agriculture. Nous montrons également que l’habitat des éléphants est négativement affecté par le braconnage et qu’actuellement les éléphants ne traversent pas la frontière entre le Ghana et la Côte d’Ivoire. Mots clés supplémentaires : Ankasa, Bia, la forêt de Goaso, le braconnage, la conservation des éléphants